2012
DOI: 10.1063/1.4730397
|View full text |Cite
|
Sign up to set email alerts
|

Superferromagnetism and coercivity in Co-Al2O3 granular films with perpendicular anisotropy

Abstract: Magnetic properties of nano-granular Co0.55–(Al2O3)0.45 films have been studied by vibrating sample magnetometry, ferromagnetic resonance, and magnetic force microscopy (MFM). The films possess a growth-induced perpendicular anisotropy related to the shape anisotropy of the granules. Being unpercolated physically, the films demonstrated a clear magnetic percolation behavior in the temperature dependence of the coercivity and MFM scans. The temperature dependence of the coercivity measured along the easy magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…In the absence of preferable crystallographic orientation of bcc α-FeCo(Zr) conrmed with XRD, the observed magnetic anisotropy is usually assigned to elongated, ellipsoidal shape of granules [27,31]. Compara- The value of eective inductive contribution to the impedance estimated basing on the correspondent equivalent circuit was found to be as high as 20 µH/µm 3 at 1 MHz that is much higher than in the case of known diodes, pnp junctions, metal semiconductor interfaces (see references in [33]).…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…In the absence of preferable crystallographic orientation of bcc α-FeCo(Zr) conrmed with XRD, the observed magnetic anisotropy is usually assigned to elongated, ellipsoidal shape of granules [27,31]. Compara- The value of eective inductive contribution to the impedance estimated basing on the correspondent equivalent circuit was found to be as high as 20 µH/µm 3 at 1 MHz that is much higher than in the case of known diodes, pnp junctions, metal semiconductor interfaces (see references in [33]).…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…The exchange interaction between the grains leads to the formation of long-range magnetic order appearing below a certain temperature [3,[23][24][25], which is called the ordering temperature T ord . For Ising model [24 and 35] the ordering temperature in granular magnets with FM coupling is related to the intergrain exchange interaction as T ord = z n H ex , where z n = 6 is the coordination number for three dimensional cubic lattice.…”
Section: A Granular Magnetsmentioning
confidence: 99%
“…Numerous papers were devoted to magnetic anisotropy and magneto-dipole interaction [15][16][17][18][19][20][21][22]. Much less is known about the exchange interaction between magnetic grains [23][24][25][26][27]. The influence of the intergrain exchange coupling on the magnetic state of the whole granular magnet are currently understood, however the microscopic picture of the intergrain exchange interaction is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…The most complicated task is the control of the intergrain distance on the scale of 1 nm. Nonetheless, several studies observed the intergrain exchange interaction of FM type with rather large value [29,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The magneto-dipole (MD) [25,26,27,28] and the exchange interactions [29,30,31,32,33] are the main intergrain coupling mechanisms in GFM. Long range MD interaction leads to the formation of super spin glass (SSG) state in the system.…”
Section: Introductionmentioning
confidence: 99%